Sustainable investments for large-scale rangeland restoration Workshop on the Global Rangelands Standard and Monitoring framework - Sustainable Investments for Large Scale Rangeland Restoration (International Livestock Research Institute, 2025)
A compilation of several presentations for a workshop on developing a global rangelands standard and global monitoring framework held at the International Rangelands Congress, Adelaide, Australia 2025, supported by the project STELARR (Sustainable Investments for Rangeland Restoration).